Perencanaan Koefisien Reduksi Daya Dukung Tanah untuk Pondasi Dangkal pada Wilayah Fluktuasi Muka Air Tanah Tinggi - Fadila Fitria Wulandari; Eko Suwarno; Edi Santoso (G-Tech: Jurnal Teknologi Terapan, 2023)
The development of housing infrastructure in Indonesia, including in Tegal Gondo Village, Karangploso, Malang, has attracted people to develop multiple levels house. However, the fluctuating soil conditions (groundwater level fluctuating) became a problem because several houses had cracks in the sloof and walls. Therefore, shallow foundation planning needs to be done by considering the reduction coefficient of soil bearing capacity. This research involved field data collection, laboratory testing, and analysis using Plaxis Version 8.2 software and manual calculations using the Terzaghi formula. The results showed a φR value (reduced soil carrying capacity) of 0.64 at a depth of -1.00 m, and a φR value of 0.55 at a depth of -2.00 m.